Recording the proportion of the carvings with centimeter grid scale - Temples of India Project Team (Jio Institute, 2024)
The centimeter grid scale is placed on the pillar to record the proportion of the carvings inside, Harshnath Temple Complex, Sikar district, Rajasthan. (Image courtesy: Mrunal Nidadavolu)